An Experiment on Building Evaluation Capacity to Address Health Inequities in China. Issue 154 (June 2017) - Zhao, Kun; Sridharan, Sanjeev; Ingabire, Marie‐Gloriose; Yu, Mo; Nakaima, April; Li, Xue; Xiao, Yue; Chen, Emily
Abstract: This paper describes an evaluation experiment conducted in China between 2013 and 2016 to use evaluative thinking and evaluation approaches to help build the salience of health equity as a performance measure for health systems. This project was informed by a realist evaluation approach that sought to understand the context, mechanisms, and outcomes underlying health inequities. This chapter describes a theory of change that includes descriptions of the key actors involved in the project, the mechanisms of impact, and short‐ and long‐term outcomes. Key questions that could help assess the impact of this project are also discussed. This paper contributes to the literature on building evaluation capacity for health inequities.